2010
DOI: 10.1007/s10895-010-0668-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Anisotropy of Branched Molecules Containing 1-Aminopyrene Chromophores

Abstract: Fluorescence anisotropy measurements were performed on a set of multichromophoric compounds, which contain a different number of aminopyrenyl moieties linked to a triazine ring, in order to reveal the nature of both the electronic excited states and relaxation pathways of the compounds. Our experimental results complement quantum chemical calculations. We propose that the lowest excited state from which fluorescence proceeds is localized on a single individual aminopyrene moiety. In contrast, excitation to a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It has been shown that the N‐substituent at the 1‐position of pyrene will cause a bathochromic shift in two of the characteristic pyrene emission bands, L b and L a , which correspond to S0→S1 and S0→S2 transitions, respectively. Furthermore, this type of substitution causes a strong increase in both the L b band intensity, and its overlap with the L a band when compared with pyrene's spectrum [51,52] . In the nematic phase, the fluorescence is strongly quenched.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the N‐substituent at the 1‐position of pyrene will cause a bathochromic shift in two of the characteristic pyrene emission bands, L b and L a , which correspond to S0→S1 and S0→S2 transitions, respectively. Furthermore, this type of substitution causes a strong increase in both the L b band intensity, and its overlap with the L a band when compared with pyrene's spectrum [51,52] . In the nematic phase, the fluorescence is strongly quenched.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this type of substitution causes a strong increase in both the L b band intensity, and its overlap with the L a band when compared with pyrene's spectrum. [51,52] In the nematic phase, the fluorescence is strongly quenched. In the solid state (the crystal forms α and β obtained from solution), no fluorescence from isolated pyrene units was observed, only a weak band centred at 575 nm was found, that may be attributed to excimer formation due to πÀ π stacking between pyrene units detected in the crystal structure of the α polymorph.…”
Section: Resultsmentioning
confidence: 99%